Representasi Nilai Budaya Masyarakat Tengger Brang Kulon dalam Motif Batik Tosarian - Izza, Siti Fitrohitul; Sukmawan, Sony (Humanis; Vol 29 No 1 (2025), 2025)
Tengger is an East Javanese community group that has a diversity of cultural values both in religious values, social values and traditions. Along with its development, this cultural value has the opportunity to be used as a local product such as Tosarian batik. In the process of creation, the Tosarian batik motif is a motif that visualizes the stylization of the form of dress-up (offering devices) and the diversity of traditions of the Tengger community, especially Tengger Brang Kulon. Based on the descriptive qualitative research method approach that focuses on the process of analyzing the background of the creation of the Tosarian batik motif, the results of this study show that Tosarian batik is a form of archiving effort that has knowledge value for the younger generation as well as an effort to preserve the local culture of the Tengger community from time to time.